Our cups are full : pottery and society in the Aegean Bronze Age : papers presented to Jeremy B. Rutter on the occasion of his 65th birthday - Gauß, Walter; Gauß, Walter; Lindblom, Michael; Lindblom, Michael; Smith, R. Angus K.; Smith, R. Angus K.; Wright, James C.; Wright, James C.; Rutter, Jeremy B. (Archaeopress, 2011)
This is a collection of papers presented to Jeremy Rutter to mark his 65th birthday